2016
DOI: 10.1016/j.cellsig.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTOR by apigenin in UVB-irradiated keratinocytes: A new implication of skin cancer prevention

Abstract: Ultraviolet B (UVB) radiation is the major environmental risk factor for developing skin cancer, the most common cancer worldwide, which is characterized by a berrant activation of Akt/mTOR (mammalian target of rapamycin). Importantly, the link between UV irradiation and mTOR signaling has not been fully established. Apigenin is a naturally occurring flavonoid that has been shown to inhibit UV-induced skin cancer. Previously, we have demonstrated that apigenin activates AMP-activated protein kinase (AMPK), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 43 publications
3
50
0
Order By: Relevance
“…Keratinocytes are the major target of UVB-induced skin damage because they serve as the predominant component in the epidermal structure. Bridgeman et al [93] found that UVB radiation activated MTOR signaling in mouse epidermal keratinocytes and in mouse skin. Syed et al [94] reported that UVB can increase MTOR phosphorylation at 1 hour after radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keratinocytes are the major target of UVB-induced skin damage because they serve as the predominant component in the epidermal structure. Bridgeman et al [93] found that UVB radiation activated MTOR signaling in mouse epidermal keratinocytes and in mouse skin. Syed et al [94] reported that UVB can increase MTOR phosphorylation at 1 hour after radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, inhibition of MTOR signaling has been observed to have the anticarcinogenesis potentiality in the UVB treated mouse model; for example, Rapamycin or apigenin treatment reduced UVB-induced epidermal proliferation through inhibiting MTOR activation [26, 93], and AZD4547 and Curcumin C3 complex suppressed UVB-induced epidermal hyperplasia via suppressing FGFR/MTOR signaling [96]. Hence, more work is needed to clarify the role of MTOR signaling in the network of UV regulated pathways, especially in the studies in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy induced by resveratrol could reduce UVB-induced apoptosis in keratinocytes, thus reducing malignant transformation [94]. Other natural components such as disaccharide trehalose and apigenin are also reported that can induce autophagy to against UVB-induced cell death [95,96]. In addition, a natural cyclopeptide, roseotoxin B, has also been demonstrated to trigger autophagy to overcome picryl chlororide-induced contact hypersensitivity in mice [97].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant activation of Akt/mTOR characterizes skin cancer development as a result of UVB radiation. Apigenin inhibited UVB-mediated mTOR activation in mouse skin and in mouse epidermal keratinocytes independent of Akt, and this led to autophagy [154]. Using 7,12-dimethyl benz[a]anthracene (DMBA)-induced experimental oral carcinogenesis golden hamsters buccal pouch model by painting 0.5% DMBA three times a week for 14 weeks, Silvan et al [155] demonstrated that oral administration of 2.5 mg/kg apigenin reduced tumor volume causing inhibition of cell proliferation, apoptosis inflammation, and angiogenesis markers, and modulation of phase I and II detoxification cascades.…”
Section: 0 Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%